Revitalisasi Alat Penukar Kalor Tipe Shell and Tube Pada Laboratorium Teknik Mesin Unsrat - Fandry Tumbade; Frans Palobo Sappu; Romels Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
Heat Exchanger is equipment used to carry out the heat exchange process due to the difference in temperature of two types of fluids that flow but do not mix. In the Unsrat Mechanical Engineering laboratory there is a Shell and Tube type heat exchanger that has not been used for practical activities for a long time because it has been damaged. This study aims to revitalize and calculate the efficiency of the heat exchanger so that it can be used in practical activities in the Mechanical Engineering laboratory of Unsrat. At the beginning of this research activity, it was found that several components were damaged, such as a malfunctioning hot water circulation pump, capacitor components and diodes on the power supply panel that experienced a short circuit and an incomplete thermometer. Then made repairs and modifications and replacement of several components. After the heat exchanger is deemed to be functioning properly, then further testing is carried out to determine the efficiency value. The results of calculations and data processing obtained efficiency of 74.38%. This provides information that the revitalization of the heat exchanger is successful and can be used as a test tool in practical activities in the Mechanical Engineering laboratory of Unsrat. Keywords: Heat exchanger, Revitalization, Shell and Tube